Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4315/0362-028x-72.3.624
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization of Ampicillin-Resistant Enterobacteriaceae Isolated from Traditional Egyptian Domiati Cheese

Abstract: The aim of this study was to address the prevalence and the molecular characteristics of antibiotic-resistant enteric bacteria isolated from one of the most popular types of Egyptian cheese. A total of 215 ampicillin-resistant enterobacterial isolates were obtained from 80 samples of Domiati cheese, and they were screened by PCR for a large pool of antibiotic resistance markers, including extended-spectrum beta-lactamases (ESBLs), class 1 and class 2 integrons, and plasmid-mediated quinolone resistance genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
2
10
2
1
Order By: Relevance
“…Although the RTE products had been produced at different places and sold at different commercial sites, no diversity was detected among the bla TEM gene family, which evidences the great spread of bla TEM-1 in these RTE types of food. Unlike the results obtained in this study, Hammad et al (2009) found diversity in b-lactamases from ampicillin-resistant enterobacterial isolates obtained from traditional Egyptian Domiati cheese. In addition to the high prevalence of different types of SHV family, these isolates also contained CTX-M-14, OXY-1, OXA-1, and CMY-4.…”
Section: Antimicrobial Susceptibility Testingcontrasting
confidence: 99%
“…Although the RTE products had been produced at different places and sold at different commercial sites, no diversity was detected among the bla TEM gene family, which evidences the great spread of bla TEM-1 in these RTE types of food. Unlike the results obtained in this study, Hammad et al (2009) found diversity in b-lactamases from ampicillin-resistant enterobacterial isolates obtained from traditional Egyptian Domiati cheese. In addition to the high prevalence of different types of SHV family, these isolates also contained CTX-M-14, OXY-1, OXA-1, and CMY-4.…”
Section: Antimicrobial Susceptibility Testingcontrasting
confidence: 99%
“…Year of collection City, country/region (one), qnrB6 (one), and qnrB20 (one) [186] qnrA, qnrB, qnrS isolates [191] qnrA, qnrB, qnrS, aac ( [194] qnrA, qnrB, qnrC, qnrS, aac(6 0 )-Ibcr, qepA (4),…”
Section: Clinical Relevance Of Pmqrmentioning
confidence: 99%
“…In addition, OXA-1 was shown to be responsible for high level resistance to ampicillin in S. Typhimurium isolates recovered from fish in India (Ruiz et al, 1999). Recently, a study conducted in Japan showed that among a series of ampicillin-resistant enterobacterial isolates recovered from traditional Egyptian Domiati cheese, some were producing OXA-1 (Hammad et al, 2009). …”
Section: Esbl And/or Ampc Encoding Resistance Genesmentioning
confidence: 99%